CARBON DIOXIDE TO CARBON MONOXIDE NICKEL-BASED ELECTROCATALYST ACTIVITY STUDY - Prasetyo, Yusuf
Carbon dioxide reutilization through reduction reaction is one promising alternative to reduce global warming. Reduction reaction of carbon dioxide is usually based on noble metals or transition metals. Recently, there is an emergence of promising nickel-based catalysts. This research focuses on examining nickel-based catalysts. Understanding the mechanism of reduction reaction on electrochemical catalysts can help in designing optimum catalysts. This study shows quantitative analysis about selectivity and activity of various nickel-based catalysts, starting from nickel surface, clusters, and single atom catalysts. Density functional theory (DFT) method implemented in Quantum Espresso software and computational hydrogen electrode model are used in this study. The goal of this thesis research is to learn reaction mechanism of carbon dioxide reduction reaction by studying its energy diagrams and charges. This study shows how nickel single atom catalyst outperforms nickel surface and clusters in carbon monoxide production. We also show how dopants can change the selectivity of carbon dioxide reaction to formate path. This research can serve as a guidance for catalysts experimentalist to synthesize a more optimum reduction reaction nickel electrocatalysts in the future.